Harnessing autophagy to overcome mitogen‐activated protein kinase kinase inhibitor‐induced resistance in metastatic melanoma. (25th November 2018) - Verykiou, S.; Alexander, M.; Edwards, N.; Plummer, R.; Chaudhry, B.; Lovat, P.E.; Hill, D.S.
Summary: Background: Patients with malignant melanoma often relapse after treatment with BRAF and/or mitogen‐activated protein kinase kinase (MEK) inhibitors (MEKi) owing to development of drug resistance. Objectives: To establish the temporal pattern of CD271 regulation during development of resistance by melanoma to trametinib, and determine the association between development of resistance to trametinib and induction of prosurvival autophagy. Methods: Immunohistochemistry for CD271 and p62 was performed on human naevi and primary malignant melanoma tumours. Western blotting was used to analyse expression of CD271, p62 and LC3 in melanoma subpopulations. Flow cytometry and immunofluorescence microscopy was used to evaluate trametinib‐induced cell death and CD271 expression. MTS viability assays and zebrafish xenografts were used to evaluate the effect of CD271 and autophagy modulation on trametinib‐resistant melanoma cell survival and invasion, respectively. Results: CD271 and autophagic signalling are increased in stage III primary melanomas vs. benign naevi. In vitro studies demonstrate MEKi of BRAF ‐mutant melanoma induced cytotoxic autophagy, followed by the emergence of CD271‐expressing subpopulations. Trametinib‐induced CD271 reduced autophagic flux, leading to activation of prosurvival autophagy and development of MEKi resistance. Treatment of CD271‐expressing melanoma subpopulations with RNA interference and small‐molecule inhibitors to CD271 reduced the development of MEKi resistance, while clinically applicable autophagy modulatory agents – including Δ9‐tetrahydrocannabinol and Vps34 – reduced survival of MEKi‐resistant melanoma cells. Combined MEK/autophagy inhibition also reduced the invasive and metastatic potential of MEKi‐resistant cells in an in vivo zebrafish xenograft. Conclusions: These results highlight a novel mechanism of MEKi‐induced drug resistance and suggest that targeting autophagy may be a translatable approach to resensitize drug‐resistant melanoma cells to the cytotoxic effects of MEKi. Abstract : What's already known about this topic? The targeted mitogen‐activated protein kinase kinase (MEK) inhibitor (MEKi) trametinib is used for the treatment of patients with BRAF ‐mutant metastatic melanoma in combination with BRAF inhibitors, but many tumours rapidly develop resistance to these drugs. Resistance of melanoma to trametinib has been associated with the induction of prosurvival autophagy, but it is unclear how stem‐cell markers, such as CD271 contribute to the transitionary phase of drug resistance. What does this study add? Transient induction of the low‐affinity neurotrophin receptor CD271 is a critical regulator of the adaptive drug‐‐response phase of melanoma cells to trametinib. Genetic or chemical inhibition of CD271 prevents emergence of trametinib‐induced drug‐resistant melanoma subpopulations. Progression to trametinib resistance by melanoma subpopulations results in loss of CD271 expression and subsequent resistance to CD271 inhibitors, but not to the cytotoxic effects of autophagy modulation. What is the translational message? Autophagy modulation either through inhibition of vacuolar protein sorting 34, or activation of cytotoxic autophagy with tetrahydrocannabinol effectively resensitizes drug‐resistant melanoma cells to trametinib in vitro and in vivo . Combined autophagy modulation and MEK inhibition offers a novel personalized therapeutic strategy to overcome MEKi‐induced drug resistance for patients with BRAF ‐mutant metastatic melanoma. Plain language summary available online Respond to this article